2019
DOI: 10.1063/1.5124139
|View full text |Cite
|
Sign up to set email alerts
|

High-order harmonic generation using quasi-phase matching and two-color pump in the plasmas containing molecular and alloyed metal sulfide quantum dots

Abstract: As high-order harmonic emitters, quantum dots are produced through laser-induced plasmas. Subsequently, we generate high-order harmonics with 800-nm and 30-fs pulses from laser-produced plasmas containing quantum dots of different metal sulfides (Ag2S, CdS, and Cd0.5Zn0.5S). The high-order harmonic generation is analyzed using different approaches, including two-color (800 nm + 400 nm) pump, application of alloyed quantum dots, and quasiphase matching of interacting waves. We discuss the self-phase modulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The most probable scenario in determining the optimal sizes of atomic aggregates for HHG is the demonstration of the attractiveness of the species with sizes of 1-5 nm, when the quantum confinement effect allows for the increase of the local field-related nonlinearity while limiting the negative effects attributed to the large (20-100 nm) nanoparticles. This assumption has recently been confirmed during the application of metal sulfide quantum dots for HHG [48,49].…”
Section: Discussionmentioning
confidence: 65%
“…The most probable scenario in determining the optimal sizes of atomic aggregates for HHG is the demonstration of the attractiveness of the species with sizes of 1-5 nm, when the quantum confinement effect allows for the increase of the local field-related nonlinearity while limiting the negative effects attributed to the large (20-100 nm) nanoparticles. This assumption has recently been confirmed during the application of metal sulfide quantum dots for HHG [48,49].…”
Section: Discussionmentioning
confidence: 65%
“…Third harmonic generation in the QD-contained media can serve as a method allowing for making a judgment about the ability of those QDs in the generation of the higher-order harmonics. Earlier, such an assumption found confirmation in the case of metal sulfide and mercury selenide QDs [ 35 , 36 , 37 ]. Our studies showed that the ITO QDs can also be used as the media for generation of the high-order harmonics in the extreme ultraviolet range.…”
Section: Discussionmentioning
confidence: 83%
“…In the present work, we were focused on the study of the nonlinear refractive indices and saturable absorption of MTQDs, rather than on the HHG in this species. However, some relations between those two effects might exist due to the correlation between the lower-order nonlinear optical properties of the studied QDs and their ability to generate strong harmonics, as has been demonstrated with some metal sulfide QDs [9,10]. Therefore, HgTe QDs can be considered as a promising material for the generation of intense harmonics in the extreme ultraviolet range.…”
Section: Discussionmentioning
confidence: 94%
“…One can assume that if the low-order, nonlinear optical properties of MTQDs, e.g., nonlinear refraction (NR) and nonlinear absorption (NA), become close to those of Ag 2 S, ZnS, Cd 0.5 Zn 0.5 S QDs, demonstrating a more efficient generation of harmonics compared to species like the InP@ZnS core-shell QDs and HgSe QDs (which show low conversion efficiencies during HHG), then a large harmonic yield will occur from mercury telluride QDs. It is worth noting that previous studies of the former group of QDs have demonstrated notable enhancements of harmonic yield compared with when HHG is carried out in plasma produced on the surfaces of bulk silver sulfide, zinc sulfide, or alloyed cadmiumzinc sulfide [9,10]. Similarly, the latter group of QDs (InP@ZnS and HgSe) demonstrating relatively weak NR and/or NA gives rise to high conversion efficiencies of the harmonics of ultrashort pulses.…”
Section: Introductionmentioning
confidence: 93%